Single staged surgical procedure for recurrent incisional hernia with trophic ulceration: a viable surgical option - Vagholkar, Ketan; Iyengar, Madhavan; Vagholkar, Suvarna (International Surgery Journal, 2016)
Incisional hernia by itself is a very challenging surgical disease to treat. Recurrent incisional hernia with trophic ulceration adds to the complexity of the problem making surgical treatment more difficult. A case of a recurrent incisional hernia with trophic ulceration treated by a single staged procedure comprising of wide excision of the trophic ulcer with repair of the incisional hernia is presented to highlight the applicability of a single staged procedure as a viable option for managing such complex hernias.